Studi In Silico Senyawa Daun Salam Sebagai Antidiabetes Melalui Mekanisme Inhibitor SGLT-2 - Amin, Saeful; Muhtar, Nenden Laila Nurafifah; Sumardiawan, Dhiyaa Kaamilah; Yulianingsih, Tipani Sri Yulianingsih (Penerbit Goodwood, 2024)
Purpose: This study aims to investigate the potential of bioactive compounds from Indonesian bay leaf (Syzygium polyanthum) as Sodium-Glucose Cotransporter-2 (SGLT-2) inhibitors for the treatment of diabetes mellitus using an in silico approach. Methodology/approach: The methodology included identifying bioactive compounds from bay leaf, preparing the SGLT-2 protein structure, molecular docking using Molegro Virtual Docker, molecular dynamics simulations with YASARA Dynamics, and data analysis focusing on rerank scores and RMSD (Root Mean Square Deviation) values. Result/findings: The in silico study revealed that several bioactive compounds in bay leaf, such as flavonoids and phenolic acids, exhibit a strong affinity and specific interaction with SGLT-2, which yielded more negative rerank scores than empagliflozin, indicating stronger binding affinity. Molecular dynamics simulations confirmed the stability of ligand-protein binding, particularly for 3,4-dicaffeoylquinic acid. Conclusions: Bay leaf compounds like flavonoids and phenolic acids showed strong binding to SGLT-2, with better rerank scores than empagliflozin. Molecular dynamics confirmed stable interactions, especially for 3,4-dicaffeoylquinic acid. Limitations: This study is limited by variations in dosage and treatment duration in existing research, the use of animal models that do not fully replicate human type 2 diabetes, and the need for further in vitro and in vivo validation. Contribution: This study supports bay leaf as a potential antidiabetic phytopharmaca via SGLT-2 inhibition. In silico methods aid drug discovery and align with evidence of its blood sugar-lowering effects. Further in vitro and in vivo studies are needed to confirm efficacy and safety.